Energy audit: types, scope, methodology and report structure - Pankaj Sharma; Surender Reddy Salkuti; Seong-Cheol Kim (Institute of Advanced Engineering and Science, 2021)
The objective of this paper is to study various methods adopted during the energy audit. Many countries are focusing on energy, not only enhancing the tenable power generation sources but also on utilizing the power more proficiently for economic utilization. The energy audit is an important parameter for all the developing and developed countries and they focus on energy efficiency, energy quality, and energy intensity. In the industrial, residential, and commercial sectors the top operating expense is found to be are material, machine, manpower, and energy. Identification of the energy-consuming sector is the prior attention to look for the energy-saving potential and quality improvement. Implementation of an energy audit can enhance the efficiency, quality of power, reduce the tariff of bills, and reduces the wastage of energy. The need for energy audits, different types of energy audits, various types of software used, and the energy audit report structure were presented in this paper.